ANALISIS SEMIOTIKA ROLAND BARTHES PADA VISUAL TENUN BADUY SEBAGAI IDENTITAS DESAIN ETNIK KONTEMPORER - Gardian Tristiawan; Agustina Kusuma Dewi (CandraRupa : Journal of Art, Design, and Media, 2026)
The Baduy Woven Cloth is a cultural artifact containing a pure visual communication system from the Kanekes tribe. As a product of tangible culture, Baduy weaving contains cultural values ​​that can be internalized in contemporary life. Refers to that, this research aims to decode the visual meaning (motifs and colors) of the Baduy Dalam and Baduy Luar Woven Cloth as a design identity that can be transformed into a contemporary ethnic design identity. Using a qualitative method, this study combines two approaches: Roland Barthes' Semiotics to analyze the Denotation and Connotation of colors (White, Black, Dark Blue) and Jakob Sumardjo's Paradoxical Aesthetics to examine the construction of linear motifs. The analysis reveals that the Baduy Woven Cloth contains an essential spatial duality structure, aligned with the Triple Pattern concept found in the Javanese Wayang Gunungan. This visual represents the vertical (heavenly) and horizontal (worldly) concepts unified by a transitional space or inner space (pembatinan), which collectively articulates a narrative of harmony and cultural obedience (Pikukuh). This result offers a framework for Visual Communication Design (VCD) to interpret the philosophical richness of the Baduy into Slow Design concepts and authentic visual branding for the younger generation. The findings of this study will then become the initiation for designing relevant visual communication media to recontextualize the values ​​and philosophical meaning of Baduy woven cloth.